2014
DOI: 10.1038/srep05185
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of age-related structural integrity in neurons by protein with tau-like repeats (PTL-1) is cell autonomous

Abstract: PTL-1 is the sole homolog of the MAP2/MAP4/tau family in Caenorhabditis elegans. Accumulation of tau is a pathological hallmark of neurodegenerative diseases such as Alzheimer's disease. Therefore, reducing tau levels has been suggested as a therapeutic strategy. We previously showed that PTL-1 maintains age-related structural integrity in neurons, implying that excessive reduction in the levels of a tau-like protein is detrimental. Here, we demonstrate that the regulation of neuronal ageing by PTL-1 occurs vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…We previously showed that PTL-1 regulates neuronal and organismal aging (Chew et al ., 2013 , 2014 ), and now show that it modulates the stress response via SKN-1. Given that tau pathology has also been linked to oxidative stress, our findings provide an interesting avenue for a further investigation into the role of a tau-like protein in stress tolerance and longevity.…”
Section: Introduction Results and Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…We previously showed that PTL-1 regulates neuronal and organismal aging (Chew et al ., 2013 , 2014 ), and now show that it modulates the stress response via SKN-1. Given that tau pathology has also been linked to oxidative stress, our findings provide an interesting avenue for a further investigation into the role of a tau-like protein in stress tolerance and longevity.…”
Section: Introduction Results and Discussionmentioning
confidence: 57%
“…Loss of ptl-1 causes neuronal and organismal aging defects (Chew et al ., 2013 , 2014 ). As aging and stress pathways are intimately linked, we tested whether ptl-1 mutant animals are stress-sensitive.…”
Section: Introduction Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, genetic analyses revealed that PTL-1 is involved in neuronal aging, stress responses, and lifespan regulation. [23][24][25] With its limited number of cells that constitute an animal, C. elegans will be useful to determine the sites of MAP actions. The scope of this approach is not restricted to PTL-1 and MAP2/ MAP4/τ, as we hypothesize that all AP-sequence bearing proteins interact with microtubules via similar mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically it has been shown that the mutations reduce microtubule binding and facilitate Tau polymerization [109,110] elegans where the Tau homologue Ptl-1 has been shown to regulate structural neuronal integrity [112,113].…”
Section: Introductionmentioning
confidence: 99%